“The Fellowship of Compassion”, or Freemasons in late 19th – early 20th Century Lithuanian Periodical Press - Kotryna Rekašiūtė (Knygotyra, 2025)
This article presents Lithuanian publications related to the Masonic society which appeared in the late 19th and early 20th century Lithuanian periodical press (both in Prussian Lithuania and in the Lithuanian lands of the Russian Empire). It discusses the image of Freemasons in the press dedicated to Lithuanian lands in both empires. The study presents the number of publications released in of the two Lithuanian territories under discussion and identifies the periodicals that published them. It also reveals the cultural context of Masonic-related publications in the periodical press (indicating the authors of the publications, the names of periodical editors, and discussing their connection to the cultural world). The topic of Freemasonry-related Lithuanian publications in the periodical press has not been discussed in detail until now.